Optimizing microbiota profiles for athletes - Mancin, L.; Rollo, I.; Mota, J. F.; Piccini, F.; Carletti, M.; Susto, G. A.; Valle, G.; Paoli, A. (Exercise and Sport Sciences Reviews, 2020)
Gut microbiome influences athletes` physiology, but because of the complexity of sport performance and the great intervariability of microbiome features, it is not reasonable to define a single healthy microbiota profile for athletes. We suggest the use of specific meta-omics analysis coupled with innovative computational systems to uncover the hidden association between microbes and athlete`s physiology and predict personalized recommendation.